Theoretical problems in cavity nonlinear optics - Mandel, P. 1942- (Cambridge studies in modern optics, 1997)
The scientific and technological importance of lasers has generated great interest in the field of cavity nonlinear optics. This book provides a thorough description of this subject in terms of modern dynamical systems theory. Throughout, the emphasis is on deriving analytical results and highlighting their physical significance. The early chapters introduce the physical models for active and passive cavities. In later chapters, these are applied to a variety of problems in laser theory, optical bistability and parametric oscillators. Subjects covered include scaling laws, Hopf bifurcations, passive Q-switching, and Turing instabilities. Several of the topics treated cannot be found in other books, including swept control parameter dynamics, laser stability, multimode rate equations, and antiphase dynamics. The book stresses the connections between theoretical work and actual experimental results, and will be of great interest to graduate students and researchers in theoretical physics, nonlinear optics, and laser physics